Surface modification of activated carbon with silver nanoparticles for electrochemical double layer capacitors. (October 2022) - Jain, Amrita; Michalska, Monika; Zaszczyńska, Angelika; Denis, Piotr
Abstract: In the present work, we report the synthesis of surface modified activated carbon (AC). The surface of the activated carbon have been modified by using silver nanoparticles. The synthesis process is simple, cost effective and environment friendly. The modified-AC powders have been characterized by using X-ray diffraction, scanning electron microscopy and surface area and pore size measurements. The electrochemical performance of the prepared materials have been tested by fabricating symmetric configuration of EDLC by using magnesium-ion based polymer electrolytes. The cells have been tested by using cyclic voltammetry, electrochemical impedance spectroscopy and galvanostatic charge-discharge technique. AC with 3 wt% of silver presents best results with specific capacitance of the order of 398 F g −1 energy density and power density of 55 Wh kg −1 and 2.4 kW kg −1 making it an interesting material for supercapacitor application. Graphical abstract: The surface of the activated carbon has been modified by Ag NPs and tested for electrochemical double layer capacitors. Magnesium ion based polymer electrolytes has been used as an electrolyte materials. EDLC cells offered a specific capacitance of 398 F g -1 with energy and power density of 55 Wh kg -1 and 2.4 kW kg -1 . Unlabelled Image